2000
DOI: 10.1002/1522-2675(20000705)83:7<1542::aid-hlca1542>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylidene Carbenes, Part 29 , Insertion into B−C and Al−C Bonds: Glycosylborinates, -boranes, and -alanes

Abstract: Insertion of the glycosylidene carbenes derived from the diazirines 1, 14, and 15 into the BÀalkyl bond of the B-alkyl-9-oxa-10-borabicyclo[3.3.2]decanes 5, 6, and 7 yielded the stable glycosylborinates 8/9 (55%, 55 : 45), 10/11 (31%, 65 : 35), 12/13 (47%, 60 : 40), 16/17 (55%, 55 : 45), 18/19 (47%, 45 : 55), and 20/21 (31%, 30 : 70). Crystal-structure analysis of 17 and NOEs of 9 and 19 show that 17, 9, and 19 adopt similar conformations. The glycosylborinates are stable under acidic, basic and thermal condit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Thus, 3-methyl-2-cyclohexenone 128 formed 70% of diol via β-oxyalkylborane 129 (Scheme 57) [79][80][81][82]. Piperitone 130 formed a mixture of trans-diequatorial diols in equal quantities also via β-oxyalkylborane 131 [72]. The same reaction was found for 5-phenyl-2-cyclohexenone 132 which was transformed to the corresponding diols via β-boryl alkyl ether 133 [81].…”
Section: Hydroboration Of Cyclohexenone Derivativesmentioning
confidence: 72%
See 1 more Smart Citation
“…Thus, 3-methyl-2-cyclohexenone 128 formed 70% of diol via β-oxyalkylborane 129 (Scheme 57) [79][80][81][82]. Piperitone 130 formed a mixture of trans-diequatorial diols in equal quantities also via β-oxyalkylborane 131 [72]. The same reaction was found for 5-phenyl-2-cyclohexenone 132 which was transformed to the corresponding diols via β-boryl alkyl ether 133 [81].…”
Section: Hydroboration Of Cyclohexenone Derivativesmentioning
confidence: 72%
“…Vasella et al [71][72][73] showed that the insertion of glycosylidene carbenes into a boron-carbon bond of BEt 3 led to unstable glycosyl boranes, while insertion into a boron-carbon bond of boronic esters yielded stable anomeric glycosyl borinates. The glycosylidene carbenes were generated by thermolysis or photolysis of glycosylidene diazirines.…”
Section: Synthesis Of Glycosyl Boranes and Borinatesmentioning
confidence: 99%
“…Therefore, the Suzuki–Miyaura coupling reaction was employed to construct C-arylated (or vinylated) glucal derivatives 2 from C1-sp 2 pinacol boronate 6 (Figure B). This provides access to 2-deoxy-β- C -glucosides . As for C1-sp 3 glycosyl boronates, surprisingly, simple C-1 borylated monosaccharides have not been reported, except for C-1 alkylated and B-substituted monosaccharides prepared by the B–C bond insertion reaction of a glycosyl diazirine. , We envisioned that potassium β-glycosyltrifluoroborates such as 7 , which are obtainable by hydrogenation of sp 2 -boronate such as 6 (Figure C), would undergo a Ni-catalyzed metallaphotoredox coupling reaction with aryl or vinyl halides. Single-electron oxidation of 7 would generate glycosyl radical 8 , which is expected to adopt a standard chair conformation with α-radical orientation stabilized by the inner cyclic oxygen atom. Then, stereoinvertive coupling should proceed to give 5α selectively (Figure S1). , This approach would be complementary to the method via compound 2 and might be useful to synthesize analogues of native 2-deoxy glycosides (usually β- O -glycosides).…”
mentioning
confidence: 99%
“…13 As for C1-sp 3 glycosyl boronates, surprisingly, simple C-1 borylated monosaccharides have not been reported, except for C-1 alkylated and B-substituted monosaccharides prepared by the B−C bond insertion reaction of a glycosyl diazirine. 14,15 We envisioned that potassium β-glycosyltrifluoroborates such as 7, which are obtainable by hydrogenation of sp 2 -boronate such as 6 (Figure 1C), would undergo a Ni-catalyzed metallaphotoredox coupling reaction with aryl or vinyl halides. 16−18 Single-electron oxidation of 7 would generate glycosyl radical 8, 2 which is expected to adopt a standard chair conformation with α-radical orientation stabilized by the inner cyclic oxygen atom.…”
mentioning
confidence: 99%
“…and 57.9(3)8, respectively. Furthermore, the diaziridine ring does not pivot about C (1) in an attempt to bring one of the N-atoms closer to an ideal axial or equatorial position; rather the mid-point of the NÀN bond almost bisects these positions. The angles between the plane defined by O(5)ÀC(1)ÀC (2), and the C(1)ÀN(1) and C(1)ÀN(2) vectors are 33.0(4) and 32.0(3)8, respectively.…”
mentioning
confidence: 99%